2008
DOI: 10.1007/s10696-008-9053-9
|View full text |Cite
|
Sign up to set email alerts
|

Process flexibility: design, evaluation, and applications

Abstract: One of the most effective ways to minimize supply/demand mismatch cost, with little increase in operational cost, is to deploy valuable resources in a flexible and timely manner to meet the realized demand. This notion of flexible processes has significantly changed the operations in many manufacturing and service companies. For example, flexible production system is now commonly used by automobile manufacturers, and work force cross-training system is by now a common practice in many service industries. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 34 publications
2
38
0
1
Order By: Relevance
“…To answer this question, the academic community started to develop flexibility design indices, following the original index developed in Jordan and Graves (1995), which we will refer to as the JG index. Other well-known indices include the Structural Flexibility index in Iravani et al (2005), WS-APL index in Iravani et al (2007), gMeasure in Graves and Tomlin (2003), and the Expansion index in Chou et al (2008). We refer the readers to , for a complete description of these indices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To answer this question, the academic community started to develop flexibility design indices, following the original index developed in Jordan and Graves (1995), which we will refer to as the JG index. Other well-known indices include the Structural Flexibility index in Iravani et al (2005), WS-APL index in Iravani et al (2007), gMeasure in Graves and Tomlin (2003), and the Expansion index in Chou et al (2008). We refer the readers to , for a complete description of these indices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…generalized these chaining configurations that utilize level-2 flexible resources to D-skilled chains that consist of level-D flexible resources and showed that these configurations perform well in serial production lines. In recent work, Chou et al (2008) used the concept of graph expansion to construct flexible configurations that work well in newsvendor networks.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there is a mix-up risk, and an increased number of models could also give greater complexity and more work in progress. According to [32], there is a trade-off between the level of flexibility available in the system and the associated complexity and operating costs. The challenge is to have the "right" level of flexibility to capture Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4 Potential for reduction of weld metal weight in the process of welded structures the benefits from a fully flexible system while controlling the increase in implementation costs. A slight increase in process flexibility can lead to a significant improvement in system performance [32].…”
Section: Discussionmentioning
confidence: 99%